Contraintes spatiales et enjeux territoriaux d’une déclinaison régionale de la transition énergétique : l’exemple de la région Provence-Alpes-Côte d’Azur - Maximin Chabrol; Loïc Grasland (VertigO)
The question of energy transition now arises at regional and local scales, while the problem of supply and energy transport remained until there a national responsibility in most countries. Energy transition involves reconsidering the links between energy production and consumption and evaluating potential production and implementation of renewable energy and energy efficiency. The territory is a critical reflection field, without that we can answer immediately to the question of scale. What are the spatial and territorial implications of regional variation of the energy transition, and how territorialize issues? This paper proposes to consider this question in a potential renewable energy production and energy consumption analysis in the Provence-Alpes-Côte d'Azur area (PACA) in France.